2018
DOI: 10.3390/nu10030353
|View full text |Cite
|
Sign up to set email alerts
|

Glycycoumarin Sensitizes Liver Cancer Cells to ABT-737 by Targeting De Novo Lipogenesis and TOPK-Survivin Axis

Abstract: Glycycoumarin (GCM) is a representative of bioactive coumarin compounds isolated from licorice, an edible and medicinal plant widely used for treating various diseases including liver diseases. The purpose of the present study is to examine the possibility of GCM as a sensitizer to improve the efficacy of BH3 mimetic ABT-737 against liver cancer. Three liver cancer cell lines (HepG2, Huh-7 and SMMC-7721) were used to evaluate the in vitro combinatory effect of ABT-737/GCM. HepG2 xenograft model was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…From 8-week to 20-week of the STAM mice model, we used small-molecule inhibitors targeting LPL, FABP4 or CPT1 for intervention. By reviewing the literature, the concentrations of small-molecule inhibitors Orlistat, BMS309403 and Etomoxir were determined to be 100 mg/kg [42] , 15 mg/kg [43,44] and 15 mg/kg [45,46]. We observed that the intraperitoneal injection of small-molecule inhibitors could effectively reduce the number and size of liver tumors in STAM mice, indicating that NASH-related tumorigenesis and tumor growth were inhibited.…”
Section: Discussionmentioning
confidence: 96%
“…From 8-week to 20-week of the STAM mice model, we used small-molecule inhibitors targeting LPL, FABP4 or CPT1 for intervention. By reviewing the literature, the concentrations of small-molecule inhibitors Orlistat, BMS309403 and Etomoxir were determined to be 100 mg/kg [42] , 15 mg/kg [43,44] and 15 mg/kg [45,46]. We observed that the intraperitoneal injection of small-molecule inhibitors could effectively reduce the number and size of liver tumors in STAM mice, indicating that NASH-related tumorigenesis and tumor growth were inhibited.…”
Section: Discussionmentioning
confidence: 96%
“…Among them, Resveratrol inhibits the invasion and metastasis of colon cancer through reversal of EMT via the AKT/GSK-3β/Snail signaling cascade (Yuan et al, 2019). Moreover, Wogonin (Tian et al, 2014), Ursolic acid (Yan et al, 2010), Zerumbone (Samad et al, 2018), 6-Gingerol (Weng et al, 2010), Coumarin (Zhang E. et al, 2018), Resveratrol (Gao et al, 2020), Rutin (Thomas et al, 2017), Oleanolic acid (Wang et al, 2018) were involved in regulating the proliferation, apoptosis, invasion, as well as metastasis of HCC. Oleanolic acid serves an anti-EMT effect in HCC by increasing iNOS dimerization, NO production, and NT of EMT-related proteins (Wang H. et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our study with the sensitization effect of GCM on ABT‐737 demonstrated that the phosphorylation levels of AMPK and ACC (inhibitory phosphorylation) were enhanced by either GCM alone or the combination, indicating the key lipogenic enzyme activity of ACC was suppressed by GCM. Furthermore, we found that inhibition of ACC by its inhibitor orlistat led to significant increase of ABT‐737‐induced apoptosis of liver cancer cells in vitro and enhanced tumor growth inhibition in vivo (Zhang et al, ). These results indicated that the inhibition of ACC by GCM may contribute to its sensitization effect on ABT‐737.…”
Section: Mechanisms Involved In the Hepatoprotective Effect Of Gcmmentioning
confidence: 97%